Contextualizing the NCS through the use of school gardens in the Butterworth area - Rasi, Nandi (Rhodes University, Faculty of Education, Department of Education, 2009)
The research focuses on how teachers can use school gardens sponsored by South African National Biodiversity Institute as resource materials for teaching and learning. The study also focused on how teachers can integrate local knowledge into the school curriculum. The setting of the research is Zizamele Senior Primary School situated in Zizamele community in Butterworth in the Eastern Cape. The study is designed in portfolio format. It consists of three separate studies: a contextual profile; a stakeholder analysis; and a small-scale action research project, which build on each other. By developing a contextual profile of the research site, and the school community and school gardens project, I was able to collect information that informed the stakeholder analysis and the action research study. Data for the contextual profile was gathered by using a variety of data gathering techniques like questionnaires and interviews. The findings were that: the study area is characterized by socio-economic issues like poverty, unemployment, drug abuse and crime. This requires that the people of the area take responsibility in addressing some of the problems by being involved and knowing where to report issues. The second study, which is the stakeholder analysis, was done to mobilize stakeholders' contributions to the gardens project in Zizamele School, sponsored by the South African National Biodiversity Institute. Data was collected at meetings and workshops in the schools through interviews. Findings indicated that different stakeholders had various contributions to make and that they were prepared to work with the school and with each other to develop the school garden and the learning potential of the school garden. This paved the way for the small scale action research case study that would follow. The last study, the small scale action research, was undertaken in the same school, Zizamele School, and focused on investigating ways of integrating local knowledge into the curriculum and how teachers use the gardens as resource for teaching and learning, with reference to Life Orientation Learning Area. Data was collected by interviews, questionnaires and worksheets. The study involved two teachers who worked with me on the action research and Grade 5 and 6 learners, as well as some of the community stakeholders. The main finding of the action researched showed the potential for involving community members in the process of integrating local knowledge as a way of implementing aspects of the Life Orientation curriculum requirements. The three studies link with each other, and show that to start with an action research project, one needs to understand the context, and the roles of different stakeholders, and how they might contribute to the programmes in the school. Findings showed that teachers could use gardens as resource materials for teaching and learning, and that they could bring in local knowledge to the school curriculum.
Keywords: South African National Biodiversity Institute; Environmental education -- South Africa; School gardens -- South Africa -- Butterworth; Gardening -- Study and teaching (Elementary) -- South Africa -- Butterworth; Environmental education -- Study and teaching (Elementary) -- South Africa -- Butterworth; Teacher participation in curriculum planning -- South Africa -- Butterworth